Massive Stokes shift in 12-coordinate Ce(NO2)63−: crystal structure, vibrational and electronic spectra. Issue 1 (December 2018) - Luo, Yuxia; Hau, Chun-Kit; Yeung, Yau; Wong, Ka-Leung; Shiu, Kwok; Tanner, Peter
Abstract The Ce3+ ion in Cs2 NaCe(NO2 )6 (I ), which comprises the unusualT h site symmetry of the Ce(NO2 )6 3− ion, demonstrates the largest Ce-O Stokes shift of 8715 cm−1 and the low emission quenching temperature of 53 K. The activation energy for quenching changes with temperature, attributed to relative shifts of the two potential energy curves involved. The splitting of the Ce3+ 5d1 state into two levels separated by 4925 cm−1 is accounted for by a first principles calculation using the crystal structure data ofI . The NO2 − energy levels and spectra were investigated also in Cs2 NaLa(NO2 )6 and modelled by hybrid DFT. The vibrational and electronic spectral properties have been thoroughly investigated and rationalized at temperatures down to 10 K. A comparison of Stokes shifts with other Ce-O systems emphasizes the dependence upon the coordination number of Ce3+ .